Autism common variants associated with white matter alterations at birth: cross-sectional fixel-based analyses of 221 European term-born neonates from the developing human connectome project - Hai Le; Alexandra F. Bonthrone; Alena Uus; Daphna Fenchel; Alexandra Lautarescu; Konstantina Dimitrakopoulou; A. David Edwards; Joseph V. Hajnal; Serena J. Counsell; Lucilio Cordero-Grande; Daan Christiaens; Dafnis Batalle; et al. (Translational Psychiatry)
Abstract Increasing lines of evidence suggest white matter (WM) structural changes associated with autism can be detected in the first year of life. Despite the condition having high heritability, the relationship between autism common genetic variants and WM changes during this period remains unclear. By employing advanced regional and whole-brain fixel-based analysis, the current study investigated the association between autism polygenic scores (PS) and WM microscopic fibre density and macrostructural morphology in 221 term-born infants of European ancestry from the developing Human Connectome Project. The results suggest greater tract mean fibre-bundle cross-section of the left superior corona radiata is associated with higher autism PS. Subsequent exploratory enrichment analysis revealed that the autism risk single nucleotide polymorphisms most associated with the imaging phenotype may have roles in neuronal cellular components. Together, these findings suggest a possible link between autism common variants and early WM development.